The effect of dibenzo-p-dioxin- and dibenzofuran-contaminated soil on the earthworm Eisenia andrei - Roubalová, Radka; Dvořák, Jiří; Procházková, Petra; Elhottová, Dana; Rossmann, Pavel; Škanta, František; Bilej, Martin (Environmental pollution (Barking, Essex, 2014)
Polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) belong to the group of persistent organic pollutants, highly toxic environmental pollutants that include hydrophobic compounds with the tendency to bioaccumulate. Earthworms (Eisenia andrei) were exposed to PCDD/Fs-contaminated soil, and changes in their lipophilic structures and the gene expression of their defense molecules were followed. Damage to the intestinal wall and adjacent chloragogenous tissue was observed. Further, the up-regulation of the expression of several genes was detected. On the basis of these results, the mechanism of the impact of PCDD/Fs on earthworms has been proposed. Dioxins that accumulate in the lipophilic structures cause an increase in reactive oxidative species that triggers oxidative stress followed by the gene expression of two molecules that play a role in protection against oxidant toxicity, calreticulin (CRT) and Hsp70. Moreover, the effect of microbial biomass on the expression of coelomic cytolytic factor (CCF), a pattern recognition receptor, was also observed.
Keywords: Animals; CCF; ROS; Soil Pollutants; Oligochaeta; látky znečišťující půdu; Calreticulin; benzofurany; Eisenia andrei; Benzofurans; regulace genové exprese; Hsp70; Dioxins; Chloragogenous tissue; Gene Expression Regulation; zvířata; Soil; půda; dioxiny; PCDD/Fs